0223 Anxiety Levels In Simulated Versus Real Ward Rounds. (1st November 2014) - Hall, Thomas; Voll, Jessika; Bragg, Damian
Abstract : Background/context: Final year medical students at Nottingham University Medical School participate in a simulated ward-round. The focus of the simulation is on assuming the role of an F1 doctor, and completing administrative tasks arising from the ward round. We set out to determine whether the course replicated similar anxiety levels to that of a real ward round. Methodology: 38 participants of the simulated ward round were given questionnaires consisting of 10 likert-scale statements pertaining to their emotional response to a simulated ward round, and to a real ward round. Results/outcomes: 22 out of 38 students responded (58%). Students felt more observed on the simulated round (71.4% vs 18.2%), however, the anxiety caused by the registrar/consultant was the same in both (42.9%). Students' confidence in what to do was similar in both rounds (42.9% in sim vs 38.1%), however, students who took part in the sim round first were far more confident in their real ward rounds (60.0% vs 31.3%) however stress levels were unchanged. Students were also happier making mistakes in the sim round (71.43% vs 27.2%) Conclusions and recommendations: While everyone is rightly enthusiastic about the learning outcomes in simulation teaching, we must be mindful of the psychological effects of scrutiny and "simulation stress" on students and their detrimental effects on learning. This simulation appears to have been no more stressful than a typical ward round, and if done in advance, enables students to approach real ward rounds with more confidence. We plan to follow this up by further quantifying stress levels in both environments. References: Cleave-Hogg, et al . "Experiential learning in an anaesthesia simulation centre: analysis of students' comments." Medical teacher 24.1 (2002): 23–26 Paskins, et alet al. "Final year medical students' views on simulation-based teaching: a comparison with the Best Evidence Medical Education Systematic Review." Medical teacher 32.7 (2010): 569–577 Firth. "Levels and sources of stress in medical students." British medical journal (Clinical research ed.) 292.6529 (1986) Ziv, et al . "Simulation based medical education: an opportunity to learn from errors." Medical teacher 27.3 (2005): 193–199 Sarikaya, et al . "The anxieties of medical students related to clinical training." International journal of clinical practice 60.11 (2006): 1414–1418